2015
DOI: 10.1007/s12015-015-9587-7
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Based Therapy in Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis is a progressive fibrosing disorder for which there is no cure and no pharmacological treatment capable of increasing in a meaningful way the survival rate. Lung transplantation remains the only possible treatment for patients with advanced disease, although the increase in 5-year survival is only 45 %. Some preclinical studies have generated promising results about the therapeutic potential of exogenous stem cells. However, two initial clinical trials involving the endobronchial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 155 publications
0
31
0
Order By: Relevance
“…A number of studies demonstrated the efficacy of mesenchymal stem cell administration in many lung diseases including acute lung injury,8 bronchopulmonary dysplasia,910 chronic obstructive pulmonary disease,1112 fibrosing pulmonary injury,1314 pulmonary ischemia reperfusion injury,15 radiation induced lung injury,16 sepsis,17 and PAH 7918. Mesenchymal stem cells have an effect on lung inflammation and injury through paracrine interactions rather than direct interaction.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies demonstrated the efficacy of mesenchymal stem cell administration in many lung diseases including acute lung injury,8 bronchopulmonary dysplasia,910 chronic obstructive pulmonary disease,1112 fibrosing pulmonary injury,1314 pulmonary ischemia reperfusion injury,15 radiation induced lung injury,16 sepsis,17 and PAH 7918. Mesenchymal stem cells have an effect on lung inflammation and injury through paracrine interactions rather than direct interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-based therapy has emerged as a central strategy in regenerative medicine and tissue engineering. Over the past few decades, various cell types, including primary cells (Kulig and Vacanti, 2004 ; Pepper et al, 2015 ), stem cells (Street et al, 2003 ; Astradsson, 2015 ; Tomatsu et al, 2015 ; Barczyk et al, 2015 ), and genetically modified cells (Kim et al, 2001 ), have been chosen as potential candidates to treat a myriad of complex diseases (e.g. diabetes (Efrat, 2008 ; Pouch, 2015 ), anemia (Orive et al, 2005 ), hemophilia (Hortelano and Chang, 2000 ) and even cancers (Cirone et al, 2002 ; Hao et al, 2005 )).…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell-based therapy, including induced pluripotent, neural, and mesenchymal stem cells (MSCs), is considered to be a potential treatment for various diseases, such as stroke, spinal cord injury, idiopathic pulmonary fibrosis, malignant glioma, diabetes, and liver disease. [9][10][11][12][13][14][15][16] In recent years, some studies have reported the protective effects of adipose-derived MSCs (ADMSCs) in the experimental treatment of AKI. 17,18 Two types of adipose tissues (brown and white adipose) usually exist to maintain energy metabolism through the storage of lipids.…”
mentioning
confidence: 99%